K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 9 2016

đề là j

(2x+1)-24=3.24

=>(2x+1)-24=48

=>(2x+1)-16=48

=>2x+1=48+16

=>2x+1=64

=>2x=64-1

=>2x=63

=>x=63:2

=>x=31,5

19 tháng 7 2017

\(\frac{2x+1}{6}=\frac{24}{2x+1}\)

Theo đề bài ta có:

\(\left(2x+1\right)\left(2x+1\right)=24.6=144\)

\(\Rightarrow\left(2x+1\right)^2=144\)

\(\Rightarrow2x+1=12\)

\(\Rightarrow2x=12-1\)

\(\Rightarrow2x=11\)

\(\Rightarrow x=\frac{11}{2}\)

\(\Rightarrow5,5\)

Vậy x = 5,5

18 tháng 7 2017

Ta có: \(\frac{2x+1}{6}=\frac{24}{2x+1}\Rightarrow\left(2x+1\right)^2=24\times6=144\)

                                                \(\Rightarrow2x+1=\sqrt{144}=12\)

                                               \(\Rightarrow2x=12-1=11\Rightarrow x=\frac{11}{2}=5,5\) 

a: Ta có: \(10-\left\{\left[\left(x:3+17\right):10+3\cdot2^4\right]:10\right\}=5\)

\(\Leftrightarrow\left[\left(x:3+17\right):10+48\right]:10=5\)

\(\Leftrightarrow\left(x:3+17\right):10+48=50\)

\(\Leftrightarrow\left(x:3+17\right):10=2\)

\(\Leftrightarrow x:3+17=20\)

\(\Leftrightarrow x:3=3\)

hay x=9

b: Ta có: \(2448:\left[119-\left(x-6\right)\right]=24\)

\(\Leftrightarrow119-\left(x-6\right)=102\)

\(\Leftrightarrow x-6=17\)

hay x=23

c: Ta có: \(165-\left(35:x+3\right)\cdot19=13\)

\(\Leftrightarrow\left(35:x+3\right)\cdot19=152\)

\(\Leftrightarrow\left(35:x+3\right)=8\)

\(\Leftrightarrow35:x=5\)

hay x=7

21 tháng 2 2022

\(\dfrac{3}{4}\left(2x-5\right)+\dfrac{1}{6}=\dfrac{5}{24}\\ \Rightarrow\dfrac{3}{4}\left(2x-5\right)=\dfrac{1}{24}\\ \Rightarrow2x-5=\dfrac{1}{18}\\ \Rightarrow2x=\dfrac{91}{18}\\ \Rightarrow x=\dfrac{91}{36}\)

21 tháng 2 2022

15/16 . -7/13 + 15/16 . -6/13 -1/16

15 tháng 10 2021

\(A=1+5^2+5^4+...+5^{2x}\)

\(\Rightarrow25A=5^2+5^4+...+5^{2x+2}\)

\(\Rightarrow24A=25A-A=5^2+5^4+...+5^{2x+2}-1-5^2-...-5^{2x}=5^{2x+2}-1\)

\(\Rightarrow A=\dfrac{5^{2x+2}-1}{24}=\dfrac{25^6-1}{24}\)

\(\Rightarrow2x+2=6\Rightarrow x=2\)

 

15 tháng 10 2021

E cảm ơn ạ

 

\(A=\left(\dfrac{2x+1}{2\left(x+2\right)}-\dfrac{x}{3\left(x-2\right)}-\dfrac{2x^2}{3\left(x-2\right)\left(x+2\right)}\right)\cdot\dfrac{24-12x}{13x+6}\)

\(=\dfrac{3\left(2x+1\right)\left(x-2\right)-2x\left(x+2\right)-4x^2}{6\left(x-2\right)\left(x+2\right)}\cdot\dfrac{12\left(2-x\right)}{13x+6}\)

\(=\dfrac{3\left(2x^2-3x-2\right)-2x^2-4x-4x^2}{x+2}\cdot\dfrac{-2}{13x+6}\)

\(=\dfrac{6x^2-9x-6-6x^2-4x}{x+2}\cdot\dfrac{-2}{13x+6}=\dfrac{2}{x+2}\)